Imagens da alma : universo simbólico em “A chuva imóvel”, de Campos de Carvalho - Carvalho, Joaquim Gama de (2012)
This dissertation is the result of an analysis performed on the novel A chuva imóvel, de Campos de Carvalho, by the bias of its affluent symbolism. Following the path of the protagonist André Medeiros, we set three moments to study the function of the symbol in the work. In the first chapter, we consider the André‟s flippancy while a being immersed in the dynamics of the dual symbolism. In an antagonistic way, the narrator-character will show his main concern: to recover the unit of an I very scattered and fragmented due to his own biography, but also, and mainly, for the meeting with the "Thing", a malignant been withal he faces. To deepen our assertions, we primarily used the writings of C. G. Jung, Mircea Eliade and Jean Chevalier (which appears in all our work with his indispensable Dictionary of Symbols). In the second chapter, we study how Andrew begins to define itself better as a bearer of individual /universal I, thanks to the encounter with the symbolic artistic creativity. As theoretical, there are excerpts by Martin Buber, MárioFerreira dos Santos, Paul Tillich. In the third and final part of our study, mainly by relying on ideas of Roberval Alves Pereira (Roberval Pereyr), we explain the fully form withal the symbol of Andrews‟s victory acts on his own destructive dimension, making his way resemble the creative activity.